Odpowiedź :
Oblicz
a)-2 i 1/5 +3,3=-2i2/10+3,3=1,1
b)1 i 5/6 - 3 i 1/3=1 i 5/6 -3i2/6=-1 i 3/6=-1,5
c)4,3 - 7,5=-3,2
d)-4,5 - 2 i 1/4 =-4,5-2,25=-6,75
e) - 3 i 1/6 - (-5 i 5/6)=2 i 4/6
f) 7 i 1/3 +(-4 i 5/6)=7 i2/6-4 i5/6=2 i 3/6=2,5
g) -5 i 4/7+ 7=-1 i3/7
h)1,23-9=-7,77
i) -6-(-4 i 5/6)=-1 i 1/6
zad2.
b)-10-7-(-7)-18=-10-7+7-18=-28
c)-5/9+2/3+5/9-5/6-2/3=-5/6
d)-2/7+3/8-1/2+2/7-1/4+1/2=3/8-2/8=1/8
e)-1,1+2,2+3,3-5,5+6,6=5,5
f)-3,7+2,85+4,7-4,85=1-2=-1
h)-1/8-1/3+2,5+3 i 1/3-(-0,125)=
-1/8-1/3+2,5+3 i 1/3-(-1/8)=
5,5
a)-2 i 1/5 +3,3=-2i2/10+3,3=1,1
b)1 i 5/6 - 3 i 1/3=1 i 5/6 -3i2/6=-1 i 3/6=-1,5
c)4,3 - 7,5=-3,2
d)-4,5 - 2 i 1/4 =-4,5-2,25=-6,75
e) - 3 i 1/6 - (-5 i 5/6)=2 i 4/6
f) 7 i 1/3 +(-4 i 5/6)=7 i2/6-4 i5/6=2 i 3/6=2,5
g) -5 i 4/7+ 7=-1 i3/7
h)1,23-9=-7,77
i) -6-(-4 i 5/6)=-1 i 1/6
zad2.
b)-10-7-(-7)-18=-10-7+7-18=-28
c)-5/9+2/3+5/9-5/6-2/3=-5/6
d)-2/7+3/8-1/2+2/7-1/4+1/2=3/8-2/8=1/8
e)-1,1+2,2+3,3-5,5+6,6=5,5
f)-3,7+2,85+4,7-4,85=1-2=-1
h)-1/8-1/3+2,5+3 i 1/3-(-0,125)=
-1/8-1/3+2,5+3 i 1/3-(-1/8)=
5,5
a)-2⅕ +3,3 = -2,2+3,3 = 1,1
b)1⅚ - 3⅓ = 1⅚-3 2/6= 11/6-20/6=-9/6=-1½
c)4,3 - 7,5 = -3,2
d)-4,5 - 2¼ = -4,5-2,25 = -6,75
e) - 3⅙ - (-5⅚) = -19/6+35/6=16/6=2⅔
f) 7⅓ +(-4⅚) = 22/3-29/6 = 44/6-29/6 = 15/6 = 2½
g) -5 i 4/7+ 7 = -39/7+49/7=10/7= 1 i 3/7
h)1,23-9 = -7,77
i) -6-(-4⅚) = -6+4⅚= -36/6+29/6=-7/6=-1⅙
zad2.
b)-10-7-(-7)-18 = -10-7+7-18=-10-18=-28 (skraca się - z 70
c)-5/9+⅔+5/9-⅚-⅔ = -⅚ (skraca się -5/9 z 5/9 i -2/3 z 2/3)
d)-2/7+3/8-½+2/7-¼+½ = ⅜-¼ = ⅜ - 2/8=⅛ (skraca się -2/7 z 2/7 i -1/2 z 1/2)
e)-1,1+2,2+3,3-5,5+6,6 = 2,2+3,3=5,5 (skraca się -1,1 i -5,5 z 6,6)
f)-3,7+2,85+4,7-4,85 = 1-2 = -1 (z działania -3,7+4,7 zostaje 1. Z 2,85-4,85 zostaje -2)
h)-⅛-⅓+2,5+3⅓-(-0,125) = -⅛-⅓+2,5+3⅓+⅛ = 3+2,5=5,5 (skraca się -1/8 z 1/8; z działania -1/3+3 1/3 zostaje 3)
b)1⅚ - 3⅓ = 1⅚-3 2/6= 11/6-20/6=-9/6=-1½
c)4,3 - 7,5 = -3,2
d)-4,5 - 2¼ = -4,5-2,25 = -6,75
e) - 3⅙ - (-5⅚) = -19/6+35/6=16/6=2⅔
f) 7⅓ +(-4⅚) = 22/3-29/6 = 44/6-29/6 = 15/6 = 2½
g) -5 i 4/7+ 7 = -39/7+49/7=10/7= 1 i 3/7
h)1,23-9 = -7,77
i) -6-(-4⅚) = -6+4⅚= -36/6+29/6=-7/6=-1⅙
zad2.
b)-10-7-(-7)-18 = -10-7+7-18=-10-18=-28 (skraca się - z 70
c)-5/9+⅔+5/9-⅚-⅔ = -⅚ (skraca się -5/9 z 5/9 i -2/3 z 2/3)
d)-2/7+3/8-½+2/7-¼+½ = ⅜-¼ = ⅜ - 2/8=⅛ (skraca się -2/7 z 2/7 i -1/2 z 1/2)
e)-1,1+2,2+3,3-5,5+6,6 = 2,2+3,3=5,5 (skraca się -1,1 i -5,5 z 6,6)
f)-3,7+2,85+4,7-4,85 = 1-2 = -1 (z działania -3,7+4,7 zostaje 1. Z 2,85-4,85 zostaje -2)
h)-⅛-⅓+2,5+3⅓-(-0,125) = -⅛-⅓+2,5+3⅓+⅛ = 3+2,5=5,5 (skraca się -1/8 z 1/8; z działania -1/3+3 1/3 zostaje 3)